Walory edukacyjne filmu. Krótka refleksja nad filmem Zawód – pracownik socjalny - Segiet, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2016)
The use of video in education has many advantages, which include among others quick and interesting information’s transfer, more attractive and modern methods and forms of work with students as well as the ability to quick update shared the knowledge and many materials. The film provides not only news and impact on intellect, but by the relevant statement of facts calls deep experiences and can become the starting point for lively discussions on important issues and problems associated with the implementation of the content within the item social pedagogy.